2019
DOI: 10.1115/1.4044609
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration and Experimental Validation of Plastic-Encased Resonant Ultrasonic Piezoelectric Actuator for Magnetic Resonance Imaging-Guided Surgical Robots

Abstract: Intra-operative medical imaging based on magnetic resonance imaging (MRI) coupled with robotic manipulation of surgical instruments enables precise feedback-driven procedures. Electrically powered nonferromagnetic motors based on piezoelectric elements have shown to be well suited for MRI robots. However, even avoiding ferrous materials, the high metal content on commercially available motors still cause distortions to the magnetic fields. We construct semicustom piezoelectric actuators wherein the quantity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The motor driving signal is typically the source of noise instead of the motor itself, as evaluated by Fischer et al [83]. Carvalho et al [84] at WPI showed that, with appropriate control electronics and replacement of the metal housing of a motor, such actuators can be used with minimal electrical noise or paramagnetic artifacts induced.…”
Section: B Piezoelectric Actuation For Mri-guided Robotsmentioning
confidence: 99%
“…The motor driving signal is typically the source of noise instead of the motor itself, as evaluated by Fischer et al [83]. Carvalho et al [84] at WPI showed that, with appropriate control electronics and replacement of the metal housing of a motor, such actuators can be used with minimal electrical noise or paramagnetic artifacts induced.…”
Section: B Piezoelectric Actuation For Mri-guided Robotsmentioning
confidence: 99%
“…Further, pi filters of high-efficiency remove highfrequency noises. Carvalho et al [68] presented custom USM with reduced metallic content replacing the casing with UL-TEM, a shaft of Derlin, and nylon screws, which resulted in lower distortions and better SNR.…”
Section: Stoianovici Et Al Developed a Novel Pneumatic Stepper Motormentioning
confidence: 99%
“…To demonstrate that image distortion related issues can be partly addressed by replacing metallic nonactive motor components from a resonant ultrasonic motor for non-metallic equivalents [273].…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%